Implementation of Environmental Management Accounting in the Waste Management Process at Az-Zahra Clinic, Karawang Regency - Nyimas Ayu Purnamasari; Lilis Lasmini; Meliana Puspitasari (International Journal of Economics and Management Research, 2025)
Environmental issues arising from medical waste have become an increasingly significant concern in the management of healthcare facilities. This study aims to examine the application of Environmental Management Accounting (EMA) in the waste management process at the Az-Zahra Clinic in Karawang Regency. The research uses a descriptive qualitative approach, with data collected through interviews, observations, and documentation studies. The results indicate that Az-Zahra Clinic has implemented waste management practices, including sorting, temporary storage, and destruction of medical waste through third-party vendors. However, the clinic’s environmental cost recording remains manual and is not integrated into its financial system, which leads to a lack of transparency and accountability. Environmental costs are currently recognized as part of general operating expenses without specific classification, and the measurement of these costs is done using the historical cost method. This study highlights the importance of integrating EMA to enhance the efficiency of waste management, improve compliance with environmental regulations, and ensure transparency in environmental cost recording. By adopting EMA, the clinic could better track and manage its environmental costs, which would contribute to improved operational efficiency and sustainability. It is recommended that the clinic develop a more integrated environmental accounting recording system to enhance the management of environmental impacts, improve the clarity of cost allocations, and support long-term sustainability in its operations. The study underscores the need for healthcare facilities to adopt systematic environmental accounting to ensure compliance with environmental standards and contribute to overall sustainability goals.